2013
DOI: 10.3201/eid1910.130728
|View full text |Cite
|
Sign up to set email alerts
|

Safe Pseudovirus-based Assay for Neutralization Antibodies against Influenza A(H7N9) Virus

Abstract: Serologic studies are urgently needed to assist in understanding an outbreak of influenza A(H7N9) virus. However, a biosafety level 3 laboratory is required for conventional serologic assays with live lethal virus. We describe a safe pseudovirus–based neutralization assay with preliminary assessment using subtype H7N9–infected samples and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 5 publications
5
52
0
Order By: Relevance
“…We have previously demonstrated that the titres quantified by Nab assay correlated well with the titres measured by traditional HI assay, using serum samples from influenza A(H7N9)-infected patients and uninfected subjects with good correlation (Spearman r=0.88) [10]. The pseudoviruses were prepared as described in our previous report [10].…”
Section: Pseudovirus-based Neutralisation Assaymentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously demonstrated that the titres quantified by Nab assay correlated well with the titres measured by traditional HI assay, using serum samples from influenza A(H7N9)-infected patients and uninfected subjects with good correlation (Spearman r=0.88) [10]. The pseudoviruses were prepared as described in our previous report [10].…”
Section: Pseudovirus-based Neutralisation Assaymentioning
confidence: 95%
“…Previous H7 subtype influenza virus infections in humans such as the influenza A(H7N7) outbreak in Netherlands in 2003 were poorly immunogenic and serodiagnosis and seroepidemiology were challenging [9]. We explored the kinetics of the serological responses to this novel virus in haemagglutination inhibition (HI) assays and in a recently developed H7N9 pseudotype virus particle neutralisation (Nab) test [10]. Viral pseudotypes have been previously shown to provide reliable correlation with conventional microneutralisation tests for influenza A(H5N1) serological studies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant H7N9 pseudovirus was produced as previously described (23) with modification. In brief, 10 7 293T cells were co-transfected with lentivirus vector pNL4-3-Luc R-E- (10 μg DNA), pVKD-HA (5 μg DNA) and pVKD-NA (5 μg DNA).…”
Section: Methodsmentioning
confidence: 99%
“…H7N9 pseudovirus was obtained through cotransfection with plasmids encoding Env-defective, luciferase-expressing HIV-1 genome (pNL4-3.luc.RE), pVKD-H7HA and pVKD-N9NA from A/Shanghai/4664T/2013 (H7N9) (Qiu et al, 2013). Pseudovirus-containing supernatant harvested 72 h posttransfection was incubated with serially diluted mouse sera at 37 uC for 1 h before adding to confluent MDCK cells in 96-well cell culture plates after washing with PBS.…”
Section: Characterization Of Recombinant Proteins By Sds-page Andmentioning
confidence: 99%